2018
DOI: 10.1016/j.jeurceramsoc.2017.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Protective nature of nano-TiN coatings shaped by EPD on Ti substrates

Abstract: A B S T R A C TThe hardness and corrosion resistance of TiN coatings, processed by Electrophoretic Deposition (EPD) to cover polished and unpolished Ti substrates, have been evaluated. A deposition time of 5 min has been enough to obtain a cohesive layer of 7-8 μm in thickness. The coatings were thermally treated in vacuum atmosphere at 1200°C for 1 h with heating and cooling rates of 5°C min The nanohardness values of the polished samples have been increased from 2.8-4.8 GPa up to 6.5-8.5 GPa. Besides, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Other studies reported that the thickness of TiN coating can be 1-5 µm [43]. The normal thickness of the TiN coating is also reported to be about 3-4 µm [36], and also 7-8 µm [26]. Generally, a thickness of about 1 µm for the PVD coatings, which was achieved in this study, is considered as a thin coating.…”
Section: Sem Observation Of the Prepared Samplessupporting
confidence: 64%
See 1 more Smart Citation
“…Other studies reported that the thickness of TiN coating can be 1-5 µm [43]. The normal thickness of the TiN coating is also reported to be about 3-4 µm [36], and also 7-8 µm [26]. Generally, a thickness of about 1 µm for the PVD coatings, which was achieved in this study, is considered as a thin coating.…”
Section: Sem Observation Of the Prepared Samplessupporting
confidence: 64%
“…TiN coating of 1.7 μm has been deposited on Ti and Ti alloy through magnetron sputtering; they observed an enhancement in mechanical properties (good resistance to scratch and hardness) [15]. The corrosion resistance and hardness of TiN coatings (7-8 μm in thickness) applied by electrophoretic deposition on Ti substrates have been evaluated by Mendoza et al [26]. It has been reported [27] that TiCN-coated NiTi parts by magnetron sputtering are capable of presenting remarkable tribological performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cui et al, describe the preparation of homogeneous and adhesive nanocrystalline TiN thin films from aqueous suspensions of TiN nanometric powders, obtaining 6 µm thick coatings after 10 min of deposition time by applying 10 V of deposition voltage [ 58 ]. More recently, Ureña [ 59 ] and Mendoza [ 60 ] prepared TiN protective coatings on Ti substrates to improve their wear resistance and to reduce the surface Young’s modulus for biomedical applications. Homogeneous coatings were obtained after 5 min by applying 90 V of deposition voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers in the literature report the study of suspensions of TiN powders in organic solvents. Mendoza et al [ 57 , 60 ] and Ureña et al [ 59 ] prepared TiN nanopowder suspensions using isopropyl alcohol as solvent and polyethilenimine (PEI) as stabilizer. Isopropanol was also used as media for the preparation of TiN-based suspensions on stainless steel substrates by EPD [ 53 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the literature, most of TiN coatings have been performed at high deposition temperatures (500-1100°C) [6,22,28,31,[33][34][35][36][37][38], which may cause mechanical, microstructural and chemical damage to the substrate [39][40][41]. Therefore, sputtering is a promising route due to easy control of deposition rate, high ionization rate, creation of high-density plasma, and preferable energy of deposition material improving the adhesion of coating layer [42].…”
Section: Introductionmentioning
confidence: 99%